PENGGUNAAN STRATEGI NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASILBELAJAR MATEMATIKAUNTUK SISWA KELAS XII MIPA 1 SMA NEGERI 1 BANGKINANG KOTA: Use of Numbered Heads Together (NHT) Strategy to Increase Learning Result of Student at Class Math XII MIPA 1 Sma Negeri 1 Bangkinang Kota - Ramdani, S.Pd Ramdani, S.Pd (UIR Press, 2018)
Classroom action research has been done in SMA Negeri 1 Bangkinang Kota in Mathematics subjects with research object of XII class MIPA 1 students in odd semester of academic year 2015/2016. This research is conducted as an effort to improve the learning result of Mathematics. The Numbered Heads Together (NHT) learning model is chosen to be applied after the observation and reflection done by the researcher. The researcher plans the action based on the observation and reflection that has been done through the compilation of learning tools based on the learning of Numbered Heads Together (NHT) consisting of test questions (repetition), observation sheet and lesson plan and other supporting learning tools. The Numbered Heads Together (NHT) learning model consists of 3 main stages: asking students to create a group of 4 members given head number 1, 2, 3, and 4. Then the question is asked to the group. The group worked together to answer the question so that all members got a turn to answer the question. This study can be completed in 2 cycles 4 meetings and two daily replications. The result of the research is the observation and recapitulation data of the test result and the completeness of the learning recapitulation showed that there has been an increase of positive student learning activity in the classroom and the increase of test average (repetition) and the increase of classical completeness from cycle 1 to cycle 2. Student activity during the process learning is observed by observers as data for evaluation and reflection. Average recapitulation of test (repetition) and learning completeness obtained from daily test value I and daily test II. Based on the result of this research, it can be concluded that the implementation of the Numbered Heads Together (NHT) learning model in class XII MIPA 1 SMA Negeri 1 Bangkinang Kota can improve the learning result of Mathematics subjects which is indicated by the average of test (repetition) and classical completeness in every cycle.